Simulation Environment for Traffic Control Systems Targeting Mixed Autonomy Traffic Scenarios - Link, Christopher; Malena, Kevin; Gausemeier, Sandra; Trächtler, Ansgar (Proceedings of the 9th International Conference on Vehicle Technology and Intelligent Transport Systems)
The development of autonomous vehicles and their introduction in urban traffic offer many opportunities for traffic improvements. In this paper, an approach for a future traffic control system for mixed autonomy traffic environments is presented. Furthermore, a simulation framework based on the city of Paderborn is introduced to enable the development and examination of such a system. This encompasses multiple elements including the road network itself, traffic lights, sensors as well as methods to analyse the topology of the network. Furthermore, a procedure for traffic demand generation and routing is presented based on statistical data of the city and traffic data obtained by measurements. The resulting model can receive and apply the generated control inputs and in turn generates simulated sensor data for the control system based on the current system state.
Keywords: Traffic Simulation; Traffic Control; Car2X; Mixed Autonomy; Autonomous Vehicles; SUMO; Sensor Simulation; Traffic Demand Generation; Routing; Traffic Lights; Graph Analysis; Traffic Observer

Online State Estimation for Microscopic Traffic Simulations using Multiple Data Sources* - Malena, Kevin; Link, Christopher; Mertin, Sven; Gausemeier, Sandra; Trächtler, Ansgar (VEHITS 2021 Proceedings of the 7th International Conference on Vehicle Technology and Intelligent Transport Systems)
The online fitting of a microscopic traffic simulation model to reconstruct the current state of a real traffic area can be challenging depending on the provided data. This paper presents a novel method based on limited data from sensors positioned at specific locations and guarantees a general accordance of reality and simulation in terms of multimodal road traffic counts and vehicle speeds. In these considerations, the actual purpose of research is of particular importance. Here, the research aims at improving the traffic flow by controlling the Traffic Light Systems (TLS) of the examined area which is why the current traffic state and the route choices of individual road users are the matter of interest. An integer optimization problem is derived to fit the current simulation to the latest field measurements. The concept can be transferred to any road traffic network and results in an observation of the current multimodal traffic state matching at the given sensor position. First case studies show promosing results in terms of deviations between reality and simulation.
Keywords: Microscopic Traffic Simulation; Online State Estimation; Mixed Road Users; Sensor Fusion; Integer Programming; Route Choice; Vehicle2Infrastructure